2015
DOI: 10.1177/0269881115613518
|View full text |Cite
|
Sign up to set email alerts
|

The separate and combined effects of monoamine oxidase A inhibition and nicotine on resting state EEG

Abstract: While nicotine is often associated with the neuropsychological effects of tobacco smoke, the robust monoamine oxidase (MAO) inhibition observed in chronic smokers is also likely to play a role. Electroencephalographically-indexed alterations in baseline neural oscillations by nicotine have previously been reported in both smokers and non-smokers, however, little is known about the effects of MAO inhibition in combination with nicotine on resting state EEG. In a sample of 24 healthy non-smoking males, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This improvement in performance suggests that with further training, animals with such lesions can overcome or suppress their perseverative habits, presumably, by developing alternate strategies supported by other PFC areas, such as the OFC. A recent study investigating the effects of neonatal lesions to the vlPFC and OFC separately or in combination demonstrated that, in the absence of a functional vlPFC in infancy, the OFC can take over and support learning skills (Malkova et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This improvement in performance suggests that with further training, animals with such lesions can overcome or suppress their perseverative habits, presumably, by developing alternate strategies supported by other PFC areas, such as the OFC. A recent study investigating the effects of neonatal lesions to the vlPFC and OFC separately or in combination demonstrated that, in the absence of a functional vlPFC in infancy, the OFC can take over and support learning skills (Malkova et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that while muscarinic blockers like scopolamine diminish the resting parieto-occipital alpha oscillations (Sannita et al, 1987 ; Sloan et al, 1992 ; Ebert et al, 1998 , 2001 ; Kikuchi et al, 1999 ; Osipova et al, 2003 ; Ramos Reis et al, 2013 ), nicotinic administration produces the reverse effect (Gilbert et al, 2000 ; Knott et al, 2000 , 2012 ; Walker et al, 2001 ; Bowers et al, 2015 ; Smith et al, 2016 ) but see (Knott and Fisher, 2007 ; Balsters et al, 2011 ; Fisher et al, 2012b ). Acetylcholine enhancers tend to increase posterior alpha power during visuospatial attentional modulations (Bauer et al, 2012 ) Figure 1c and frontal alpha during working memory tasks (Fisher et al, 2012a , 2013 ) but see (Eckart et al, 2016 ).…”
Section: Parieto-occipital Alpha Oscillations Are Modulated By a Myrimentioning
confidence: 99%
“…Although ciproxifan is H3 receptor antagonist/inverse agonist, it also reversibly inhibits monoamine oxidase A and B at higher doses (Hagenow et al, 2017). Monoamine oxidase inhibitors are reported for the enhancement of theta modulation (McNaughton et al, 2007; Smith et al, 2016). Thus, the involvement of monoamine oxidase enzyme inhibition cannot be ruled out in the effects of ciproxifan.…”
Section: Discussionmentioning
confidence: 99%